The policing of subway fare evasion in postindustrial Los Angeles - Johnson, Lallen T (Punishment & society, 2022)
According to the postindustrial policing thesis, cities that use cultural development strategies to attract new residents and visitors rely on order maintenance policing tactics to reinforce middle-class perspectives of safety and civility. This study applies that thesis to understand how shifting social structural dynamics influence the policing of fare evasion across the Los Angeles Metropolitan Transit Authority subway system. In accordance with the postindustrial perspective, results indicate that order maintenance policing is most intense at stations located in gentrifying neighborhoods; and, at the average station this form of policing is overwhelmingly directed towards Black and Latinx riders. Collectively, study findings suggest that mass transit in gentrifying areas represents a disputed resource that is policed in the interests of urban revitalization. Moreover, this treatment of fare evasion joins a growing body of penal remedies that expands the sphere of public social control, and further marginalizes disenfranchised groups.